2022
DOI: 10.1038/s41598-022-15938-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals cell cycle-related transcripts as key determinants of varietal differences in seed size of Brassica juncea

Abstract: Brassica juncea is an important oilseed crop, widely grown as a source of edible oil. Seed size is a pivotal agricultural trait in oilseed Brassicas. However, the regulatory mechanisms underlying seed size determination are poorly understood. To elucidate the transcriptional dynamics involved in the determination of seed size in B. juncea, we performed a comparative transcriptomic analysis using developing seeds of two varieties, small-seeded Early Heera2 (EH2) and bold-seeded Pusajaikisan (PJK), at three dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 111 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Common candidate genes, viz., AP2/ERF, SANT4, MYB, zinc finger domain, Protein kinases, glutathione s transferase, and homeobox domains were observed among heterotic ILs developed in different genetic backgrounds (Tables S6 and S7). Previous studies have confirmed that these candidate genes have an important role in the regulation of yield-related traits [52][53][54]. These candidate genes can be deployed in parental lines through marker-assisted selection to improve yield-related traits in hybrids after identifying suitable molecular markers.…”
Section: Candidate Genes Associated With Heterotic Genomic Segmentsmentioning
confidence: 79%
“…Common candidate genes, viz., AP2/ERF, SANT4, MYB, zinc finger domain, Protein kinases, glutathione s transferase, and homeobox domains were observed among heterotic ILs developed in different genetic backgrounds (Tables S6 and S7). Previous studies have confirmed that these candidate genes have an important role in the regulation of yield-related traits [52][53][54]. These candidate genes can be deployed in parental lines through marker-assisted selection to improve yield-related traits in hybrids after identifying suitable molecular markers.…”
Section: Candidate Genes Associated With Heterotic Genomic Segmentsmentioning
confidence: 79%